2019
DOI: 10.1136/bcr-2018-226830
|View full text |Cite
|
Sign up to set email alerts
|

Implication of frontal sinus mucocele’s location and intrasinus septation

Abstract: Mucocele of paranasal sinuses commonly affects frontal or frontoethmoidal air cells. With the evolution of endoscopic sinus surgery, the endoscopic marsupialisation has become the standard of care for these lesions. However, the external approach still has a role in selected cases of frontal sinus mucocele. The location of the mucocele and its communication with the natural outflow tract of the frontal sinus are some of the critical factors to be considered while choosing the surgical approach. We have discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, the external approach continues to have a role in selected cases of frontal sinus mucocele. 1 The location of the mucocele and its communication with the natural outflow tract of the frontal sinus are some of the critical factors to be considered when choosing a surgical approach. Since simple nasal endoscopic marsupialization cannot resolve a distal mucocele, the combined treatment of endoscopic marsupialization with an external approach was used in the surgery of case 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the external approach continues to have a role in selected cases of frontal sinus mucocele. 1 The location of the mucocele and its communication with the natural outflow tract of the frontal sinus are some of the critical factors to be considered when choosing a surgical approach. Since simple nasal endoscopic marsupialization cannot resolve a distal mucocele, the combined treatment of endoscopic marsupialization with an external approach was used in the surgery of case 1.…”
Section: Discussionmentioning
confidence: 99%
“…With the evolution of endoscopic sinus surgery, endoscopic marsupialization has become the standard of care for patients with paranasal sinus mucoceles. However, the external approach continues to have a role in selected cases of frontal sinus mucocele 1. The location of the mucocele and its communication with the natural outflow tract of the frontal sinus are some of the critical factors to be considered when choosing a surgical approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medial and intermediate mucoceles can be managed with an endoscopic approach but it may not be adequate for lateral mucoceles. [ 10 ] A meta-analysis and systematic review on the management of frontal sinus mucoceles showed that results from endoscopic and open approaches were comparable, although endoscopic approaches were being increasingly preferred. [ 11 12 ] Frontal sinus stenting is considered for recurrent lesions, extensive polyposis, FSOT stenosis by scarring or traumatic fracture, or if neo-ostium is less than 5 mm.…”
Section: Discussionmentioning
confidence: 99%